Pembelajaran Fisika Berbasis PEO (Predict-Observe-Explain) Menggunakan Metode Eksperimen Ditinjau dari Pemahaman Konsep Fisika - Fitriana, Anggi Wulan; Yuberti, Yuberti (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to determine the effect of the POE (Predict-Observe-Explain) learning model assisted by the experimental method on understanding the concepts of students of class XI science. This research is a Quasi Experiment with the design of Non-Equivalent Control Design Groups. The sample selection uses Cluster Random Sampling. The research sample was the experimental class (XI IPA 1) which applied the POE (Predict-Observe-Explain) learning model assisted by the experimental method and the control class (XI IPA 2) which applied the conventional learning model. The data collection instruments used were test instruments for understanding concepts (pretest and posttest). Based on the results of the study calculated by the t-test from the results of the posttest understanding of the control class concept of 78.75 and the experimental class of 82.75 obtained tcount more than t table (2.148 more than 2.024) with a significance value (ɑ = 0.05). So it can be concluded that Ha is accepted, meaning that there is the influence of the POE (Predict-Observe-Explain) learning model assisted by the experimental method of understanding concepts.Abstrak:Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran POE (Predict-Observe-Explain) berbantu metode eksperimen terhadap pemahaman konsep peserta didik kelas XI IPA.Penelitian ini merupakan Quasi Experiment dengan desain Non-Equivalent Control Grup Design.Pemilihan sampel menggunakan Cluster Random Sampling. Sampel penelitian yakni kelas eksperimen (XI IPA 1) yang diterapkan model pembelajaran POE (Predict-Observe-Explain) berbantu metode eksperimen dan kelas kontrol (XI IPA 2) yang diterapkan  model pembelajarankonvensional. Instrumen pengumpulan data yang digunakan yaitu instrumen tes untuk pemahaman konsep (pretest dan postest). Berdasarkan hasil penelitian yang dihitung dengan uji-tdari hasil posttest pemahaman konsep kelas kontrol sebesar 78,75 dan kelas eksperimen sebesar 82,75 memperoleh thitunglebih dari ttabel (2,148 lebih dari 2,024) dengan nilai signifikasi (ɑ = 0,05). Jadi dapat disimpulkan bahwa Ha diterima, artinya terdapat pengaruh model pembelajaran POE (Predict-Observe-Explain) berbantu metode eksperimenterhadap pemahaman konsep.